The association between emotions and public acceptance of recycled water for urban residents - Ding, Yizhe; Liu, Xiaojun (Journal of Civil Engineering and Management, 2021)
Worldwide water scarcity has prompted governments to develop alternative water resources, and public acceptance plays a critical role in the implementation of recycled water projects. The aim of this study was to explore how public acceptance can be affected by people’s emotional responses to recycled water. In study 1, the general population was divided into four groups, clustering analysis with the intensity of various emotions was conducted, and the association between emotions and acceptance was explored. In study 2, the emotions, people’s acceptance, and “objects of care” of water treatment experts were compared with those of members of the general population for further study. We found that the objects of care shortened the psychological distance between individuals and recycled water, which led people to generate specific emotions to recycled water. In a broader context, the study suggested that various emotions motivate people’s behavior to accept or oppose the use of recycled water.